The Use of Long Acting Reversible Contraceptives and the Relationship between Discontinuation Rates due to Menopause and to Female and Male Sterilizations - Jessica Mayra Ferreira; Ilza Monteiro; Sara Castro; Marina Villarroel; Carolina Silveira; Luis Bahamondes (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Abstract Introduction Women require effective contraception until they reach menopause. The long acting reversible contraceptives (LARC) and the depot-medroxyprogesterone acetate (DMPA, Depo-Provera(r), Pfizer, Puurs, Belgium) are great options and can replace possible sterilizations. Purpose To assess the relationship between the use of LARCs and DMPA and terminations ascribed to menopause and sterilizations in a Brazilian clinic. Methods We reviewed the records of women between 12 and 50 years of age attending the clinic that chose to use a LARC method or DMPA. Cumulative termination rates due to sterilization or because the woman had reached menopause were computed using single decrement life-table analysis over 32 years. We also examined all records of surgical sterilization at our hospital between the years 1980-2012. Results Three hundred thirty-two women had continuously used the same contraceptive until menopause, and 555 women had discontinued the method because they or their partners underwent sterilization. From year 20 to year 30 of use, levonorgestrel intrauterine-releasing system (LNG-IUS - Mirena(r), Bayer Oy, Turku, Finland; available since 1980), copper intrauterine device (IUD - available since 1980) and DMPA users showed a trend of cumulative higher discontinuation rates due to menopause when compared with the discontinuation rates due to sterilization. Over the study period, a steep decline in the use of sterilization occurred. Conclusion Over the past 15 years of research we have observed a trend: women usually preferred to continue using LARC methods or DMPA until menopause rather than decide for sterilization, be it their own, or their partners'. The annual number of sterilizations dropped in the same period. The use of LARC methods and DMPA until menopause is an important option to avoid sterilization, which requires a surgical procedure with potential complications.